Peran Gereja dalam Memotivasi Jemaat untuk Mencintai Alkitab - Viarine Pranata; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
Bible is the Word of God and the word is God Himself. People of God must love the Bible because it is the Word of God; so believers must have read the Bible at least once in lifetime from Genesis to Revelation. In fact, the love of Bible decreasingly, so it is time for the church to motivate God’s people to re-commit to love the Bible. The church with discipleship basis which always and regularly teach the word of God could fulfil the calling to equip all disciples to be matured in Him and could be the bride of Christ. Writer used library research qualitative methodology to conclude there are ways to motivate people of God to observe His word. Church has discipleship, Word of God learning group, build some of facilities to support People of God to learn the Bible and issue certificate for whom completely read and meditate the Word of God in certain period.